(2R, 6R)-hydroxynorketamine rescues chronic stress-induced depression-like behavior through its actions in the midbrain periaqueductal gray. (1st September 2018) - Chou, Dylan; Peng, Hsien-Yu; Lin, Tzer-Bin; Lai, Cheng-Yuan; Hsieh, Ming-Chun; Wen, Yang-Cheng; Lee, An-Sheng; Wang, Hsueh-Hsiao; Yang, Po-Sheng; Chen, Gin-Den; Ho, Yu-Cheng
Abstract: It has been widely reported that ketamine rescues chronic stress-induced depression-like behavior, but the underlying cellular mechanisms of the rapid antidepressant actions of ketamine remain largely unclear. Both male and female Sprague-Dawley rats were used and received modified learned helplessness paradigm to induce depression-like behavior. Depression-like behavior was assayed and manipulated using forced swim tests, sucrose preference tests and pharmacological microinjection. We conducted whole-cell patch-clamp electrophysiological recordings in the midbrain ventrolateral periaqueductal gray (vlPAG) neurons. Surface and cytosolic glutamate receptor 1 (GluR1) α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor expression were analyzed using Western blotting. Phosphorylated GluR1 expression was quantified using Western blotting analysis. The results showed that a single systemic administration of a ketamine metabolite (2R, 6R)-hydroxynorketamine (2R, 6R-HNK) rapidly rescued chronic stress-induced depression-like behavior and persisted for up to 21 days. Consistently, the chronic stress-induced diminished glutamatergic transmission and surface GluR1 expression in the vlPAG were also reversed by a single systemic injection of (2R, 6R)-HNK. Furthermore, bath application of (2R, 6R)-HNK increased the frequency and amplitude of miniature excitatory postsynaptic currents (mEPSCs) in the vlPAG. Further evidence for the antidepressant action of (2R, 6R)-HNK is provided by the finding that microinjection of (2R, 6R)-HNK into the vlPAG exhibited a rapid-acting and long-lasting antidepressant effect. This antidepressant effect of (2R, 6R)-HNK was prevented by the intra-vlPAG microinjection of AMPA receptor antagonist CNQX. Together, the current results provide evidence that (2R, 6R)-HNK rescues chronic stress-induced depression-like behavior with rapid-acting and long-lasting antidepressant effects through enhancement of AMPA receptor-mediated transmission in the vlPAG. Highlights: Both intraperitoneal and intra-vlPAG administration of (2R, 6R)-HNK rescue chronic stress-induced depression-like behavior. (2R, 6R)-HNK rapidly rescues chronic stress-induced depression-like behavior. Antidepressant effects of (2R, 6R)-HNK persist for up to 21 days. (2R, 6R)-HNK increases glutamate release presynaptically and surface GluR1 expression postsynaptically in the vlPAG. Blockage of AMPAR in the vlPAG antagonizes antidepressant effects of (2R, 6R)-HNK.